Abnormal 18F-FDG Uptake Detected with Positron Emission Tomography in a Patient with Breast Cancer: A Case of Sarcoidosis and Review of the Literature - Selmin Ataergin; Nuri Arslan; Ahmet Ozet; Mehmet Ali Ozguven (Case Reports in Medicine)
18F-FDG PET is a useful and sensitive imaging method for a variety of malignancies, however, the specificity is low in active infections and inflammatory diseases. We describe a female patient with stage IIIA breast cancer in first complete remission with combination chemotherapy who developed nodular formations in the lung and axilla 12 years later. Imaging studies as well as FDG PET showed nodular lesions and increased metabolic activity which was interpreted as the progression of the primary disease. She was first given combination chemotherapy and hormonal therapy but was proven thereafter to have sarcoidosis by pathologic examination and was successfully treated with corticosteroid treatment.